Early pregnancies among middle school students: Attribution of blame and the feelings of responsibility among teachers and parents - Fute, Antony; Sun, Binghai; Oubibi, Mohamed (Frontiers in Psychology, 2022)
Introduction Globally, 15% of adolescents give birth before turning 18, leading to considerable personal, social, and medical impacts on adolescents and to the general society. Objective This study aimed at exploring and comparing three psychological attributes (i.e., empathetic concern, feelings of responsibility, and attribution of blame) between parents and teachers for the phenomena. Method 672 teachers (54% females) and 690 parents (53% female) participated in the study. Results The results indicated a significant mean difference between parents and teachers on empathy (t = 5.735, p < 0.001), attribution of blame (t = 6.902, p < 0.001), and feelings of responsibility (t = 1.727, p < 0.001). Except for attribution of blame, parents’ mean scores of other variables were higher than that of teachers. Discussion Teachers’ higher attribution of blame to pregnant adolescents and lower empathetic concern raises a prominent concern over students’ healthy environment at school. Conclusion Understanding social feelings about responsibilities over adolescents’ general health is very essential, especially for fighting against the problem of early pregnancy.